The impact of the arms in para alpine slalom skiing - Steffensen, D.; Swarén, M.; Danvind, J.; Ohlsson, M. L. (Nordic Winter Sports Conference, 2020)
In para-alpine skiing the rules says that athletes which are not able to hold and use a pole is eligible to compete. This is sometimes a hard task for classifiers to determine. The aim of this study was to increase the knowledge of the biomechanics in order to inform the development towards evidence classification system. The participants, 1 para-alpine skier (17 year with congential dysmelia left forearm, world cup level) and 10 able-bodied alpine skiers (18,3 ± 1,7 years national junior skiers at national level), performed a slalom course in three different conditions, using 2 poles, one pole and no poles. During these races time and full-body kinematics was measured using 12 IMU sensors (Myomotion, Noraxon Inc., USA). The results showed that reduced number of poles increased the race-time for able-bodied athletes. For able-bodied skiers both arm and leg kinematics was impacted by number of poles. No poles gave a more up-right position and a less dynamic technique. For the para-alpine skier no difference in race-time was shown between 1 pole and 2 pole condition, while the no pole condition was slower. The kinematics for the 1 pole condition was significantly different between the para-athlete compared to the able-bodied group for many body angles, showing a more crunched body position and larger range of motion for the para-athletes. To conclude, the number of poles impact race-time and kinematics of both arms and legs. Also, the balance ability seem to be affected by reduced number of poles.